Academic Governance and Innovation Ecosystem in Chongqing: The Impact of Local Policies on R and D (Lex localis - Journal of Local Self-Government, 2024)
In order to improve the level of academic governance in Chongqing and build a good innovation ecosystem, this paper carries out correlation analysis from the perspective of local policies and research findings and obtains first-hand data in the form of questionnaires. Then, the internal relationship among academic governance, innovation ecosystem, and overall development of R&D is found, and the following assumptions are put forward. Academic governance in Chongqing can promote the improvement of the R&D level, and the innovation ecosystem is the objective environment for the development of R&D institutions in Chongqing University. Local policies, academic governance, and innovation ecosystem are the influencing factors for the development of R&D institutions. The results show that academic governance and innovation ecosystem will promote the development of R&D, and local policies are the main influencing factors, which will play a directional role in the normal development of R&D. Therefore, local governments should formulate academic governance policies and create a good normal environment for innovation.